The Role of Bioϐilms in Otitis Media with Effusion - Zeynel Öztürk; Nuray Bayar Muluk; Oğuzhan Oğuz; Sevilay Aynaci; Felicia Manole; Cemal Cİngİ (ENT Updates, 2024)
The possibility of biofilms on otitis media with effusion was reviewed. A systematic literature review was conducted using PubMed, Medline, Google, and Google Scholar search engines between 1975 and 2024. Articles dealing with “otitis media with effusion”, “children”, “treatment”, “pathophysiology”, “ventilation tube”, or “biofilms” were located through a search engine and retrieved through a query. A middle ear effusion, which can be either mucoid or serous and is not purulent, is a hallmark of OME. The eustachian tube disruption, age, and environmental factors have all been linked to OME. Inflammation, infection, effusion, and tissue hyperplasia are common pathways that might lead to OME, suggesting that it is a complex disorder. Whether attached to living or nonliving surfaces, biofilms comprise a collection of microbial cells surrounded by a matrix formed by the cells. This matrix accounts for about 90% of the dry mass of the biofilm. Microbiological biofilms evade both the host immune system and antibiotics. The fact that 70% of OME cultures are sterile has been known for a long time. Numerous data point to the ineffectiveness of antibiotic treatment in OME, suggesting that biofilm is responsible for the disease’s chronic nature. The present high rate of further surgery can be reduced by exploring new therapeutic options made possible by comprehending the function of biofilms in the genesis of OME. The most effective way to eliminate biofilms in the middle ear is to provide antibiotics locally.